EFEKTIFITAS PENYULUHAN METODE CERAMAH DAN BOOKLET TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG IMD DAN ASI EKSLUSIF - Rahmi Sari Kasoema; Suparni Suparni (Maternal Child Health Care, 2021)
Exclusive breastfeeding coverage at the Lubuk Repeat Aling health center is at 73.8% with the implementation of IMD being at 79.1% IMD plays an important role in reducing infant mortality and increasing the success of exclusive breastfeeding. This study aims to determine the effectiveness of counseling on improving the behavior of pregnant women about IMD and exclusive breastfeeding in the working area of the Labukulang Aling Health Center in 2021. This type of research is a Quast Experiment with a Pre-test and Post-test group design. The population is all 3rd trimester pregnant women in the working area of the Lubuk Repeat Aling Health Center as many as 45 mothers. The sample is 45 people. Analysis of the results was carried out using the independent Sample T Test. The results showed that the average knowledge before was 7.98, knowledge after intervention was 13.09, the mean difference was 5.111. From 45 respondents, the average attitude before the intervention was 28.49, the attitude after the intervention was 32.58, and the mean difference was 4.089. The results of the statistical test obtained p value 0.000, it can be concluded that there is an Effectiveness of Lecture and Booklet Method Counseling on the Knowledge and Attitudes of Pregnant Women About IMD and Exclusive Breastfeeding in the Working Area of the Lubuk Repeat Aling Solok Selatan Health Center in 2021. Knowledge and Attitudes of Pregnant Women About IMD and Exclusive Breastfeeding in the Work Area of the Lubuk Repeat Aling Solok Selatan Health Center in 2021. It is recommended that health services provide health education to pregnant women about IMD and exclusive breastfeeding so as to increase knowledge and attitudes of pregnant women.Reference :22 (2008-2021)Keywords: Counseling, Behavior, IMD, Exclusive Breastfeeding